1987
DOI: 10.1016/1359-0197(87)90141-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of radiation types and dose rates on selected cable-insulating materials

Abstract: 18 March 1987A series of radiation tests have been carried out on halogen-free cable-insulating and cable-sheathing materials comprising commercial LDPE, EPR, EV A, and SIR compounds. Samples were irradiated at five different radiation sources, e.g. a nuclear reactor, fuel elements, a 60 Co source, and in the stray radiation field of high-energy proton and electron accelerators at CERN and DESY. The integrated doses were within 50 to 5000 kGy and the dose rates within 10 mGy/s to 70 Gy/s. Tensile tests and gel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…For equation (1), if the change of the "x/y ratio", ∆R, is multiplied, because the ratio change only depends on the "population of radicals", the total change of the "x/y ratio" after irradiation by a mixed field can be written as follows.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For equation (1), if the change of the "x/y ratio", ∆R, is multiplied, because the ratio change only depends on the "population of radicals", the total change of the "x/y ratio" after irradiation by a mixed field can be written as follows.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of radiation on cable material is related to the total absorbed dose, which is mainly dependent on gamma rays [1]. For validity of radiation measurement, at least two operation cycles are required for the installation period.…”
mentioning
confidence: 99%
“…For polyethylene, ethylene‐propylene copolymer, and tetrafluoroethylene‐propylene copolymer, Seguchi et al found no differences in the effects of irradiation in vacuum by fast neutrons or γ‐rays . Using five different radiation sources including a nuclear reactor and a 60 Co source, Hanisch et al reported that damage of halogen‐free cable‐insulating and cable‐sheathing materials was dependent on the total absorbed dose but not on the type of radiation. However, a higher crosslink rate was observed when polystyrene was irradiated in a nuclear reactor than with γ‐rays and the chemical resistance of polycarbonate and poly(ethylene terephthalate) was observed to decrease much more markedly after exposure to neutron radiation than to γ‐rays .…”
Section: Introductionmentioning
confidence: 99%
“…Since 1980, there have been more studies on silicone rubber used in the radiation field in the United States, Japan, Germany, England, and other locations. [7][8][9][10][11][12] The focus has been on the effect of different radiation sources and dose rates versus silicone rubber, natural rubber, fluorine rubber, and so on, but they have not touched on the damage to these materials and changes in their microscopic structure. Until now, there has been no detailed study of radiation effects on open-porous silicone rubber foam.…”
Section: Introductionmentioning
confidence: 99%